Differences of Belitung Taro Flour (Xanthosoma sagittifolium) Composite on the Production of Barracuda Fish Siomay - Syifani Al Widad; Siti Fathonah (Jurnal Pendidikan Tata Boga dan Teknologi, 2026)
Siomay, a traditional snack that generally uses tapioca flour as a binding agent, requires local food-based alternatives for product diversification and nutritional value enhancement. This study analyzed the differences in the use of Belitung taro flour (Xanthosoma sagittifolium) composites on the level of preference (color, aroma, taste, texture, overall), physical parameters (color, texture), and nutritional content (protein, water content) of barracuda fish siomay. This study used a quantitative experimental method with a Completely Randomized Design with four taro flour composite treatments (0%, 25%, 50%, 75%) and two replications, and barracuda fish as the main protein source. Organoleptic assessment involved 40 semi-trained panelists. The hedonic test data obtained were analyzed using the Kruskal-Wallis test and if there were differences, they would be continued with the Mann-Whitney test. The results showed that the use of taro flour in siomay had no significant effect (p>0.05) on color, texture, aroma, taste, and overall assessment. Panelists preferred the siomay containing 25% taro flour, giving it the highest hardness and darkest color among the samples. The color and nutritional content were analyzed using Analysis of Variance (ANOVA), followed by Duncan's test to determine significant differences between the formulas. The protein content ranged from 6.34–7.62% and the moisture content from 55.81–57.28%, meeting the SNI 7756:2013 standard for fish siomay.